STRATEGI GURU DALAM PENGUATAN KARAKTER DISIPLIN PADA PESERTA DIDIK DI SMPN 56 SURABAYA - Shinta Dwi Ramadhani; Listyaningsih (Universitas Negeri Surabaya (Unesa), 2025)
Disciplined character is one of the important aspects in forming responsible and moral students. This study aims to describe teacher strategies in strengthening the disciplined character of students at SMPN 56 Surabaya with supporting and inhibiting factors. The related theory is Thomas Lickona's character education theory, which includes three aspects: moral knowing, moral feeling, and moral behavior. This study uses a descriptive qualitative approach. Data were collected through observation, in-depth interviews with discipline teachers and Guidance and Counseling teachers, and documentation. The number of informants in this study was five teachers, consisting of teachers who were members of the discipline team and Guidance and Counseling (BK) teachers. Data analysis using Miles and Huberman. The results of the study showed that teacher strategies in strengthening disciplined character include: (1) socialization of regulations (2) providing examples (role models), (3) surprise inspection and (4) giving warnings and appreciation. The supporting factors for this strategy are cooperation with law enforcement (Babinsa) and involvement between parents and community. Meanwhile, the inhibiting factor is the negative influence of the friendship environment. Keywords: Disciplinary Character, Teacher Strategy, SMPN 56 Surabaya